Temporality and Partiality. On the Problem of Dissociative Mental Process - Mikayelyan, Vladimir (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
Complete mental cognition is impossible without the separation of its normal and pathologic manifestations. Either way, the process of selfdiscovery occurs as a normal, if normal flow of mental processes, and in pathology at dissociative processes. At the level of objective data, in the case of dissociative identity disorder, we deal with a pathological process of splitting a single psychic apparatus, i.e. splitting of self-identity.